Relationship maintenance behaviors: a cross-cultural examination of emerging adults in romantic relationships - Baptist, Joyce A.; Norton, Aaron; Aducci, C. J.; Thompson, David E.; Cook, Ashley (My University, 2012)
Attachment and maintenance behaviors in romantic relationship were examined in Americans (n=324) and Malaysians (n=182). Findings indicated that avoidant attachment more strongly influenced maintenance behaviors in both countries compared to anxious attachment. Compared to the American participants, Malaysian participants reported higher anxious and avoidant attachment. Unlike the American participants, Malaysian men and women did not significantly differ in their attachment and maintenance behaviors, although men reported higher maintenance behaviors and lower avoidant attachment. There appeared to be a distinct division based on traditional sex-role socialization among the American participants whereby women did more to maintain relationships. Clinical implications are discussed.
Keywords: Relationship maintenance; Attachment; Emerging adults; Cross-cultural